Effects of gravity table utilization on seed quality of field beans - Lollato, Marco Antonio; Silva, Walter Rodrigues da (Pesquisa Agropecuaria Brasileira, 2014)
Considering the importance of using, and the difficulty of getting high quality field bean Phaseolus vulgaris, L. seed, the present work was carried out to assess the effects of gravity table on seed lots. A seed lot passed through twice in the gravity table, originating four treatments in the first time, and other four in the second time, from each of the four ones. The following analysis were done after sampling the treatments: seed moisture content, 1000 grain weight, volumetric weight, seed density, germination test, accelerated aging, purity test, stainned seed number, defective and germinated seed number, and seed health test. The results showed that the gravity table was efficient to separate the seed lots as a function of the following parameters: seed density, unitary and volumetric weight, germination power, vigor, seed health, and purity. These parameters were higher in the upper unloading beaks. Also a tendency of stainned, detective, germinated, Rhizoctonia solani and Fusarium spp., contaminated seeds to go to the lower unloading beak was observed. These factors justify the use of gravity table to obtain significantly better physical, physiological, and healthier seed lots from the upper unloading beak.
Keywords: Phaseolus vulgaris; processing